C2.4 Historic breakthrough in the treatment of spinal muscular atrophy (5q-sma): nusinersen (spinraza) is the first drug approved for sma. (4th October 2017) - Scoto, M; Main, M; Munot, P; Manzur, A; Muntoni, F
Abstract : Background: Classic proximal 5q-SMA is a progressive motor neuron disorder leading to muscle weakness and atrophy and is the most common genetic cause of infantile mortality, with an incidence of 1/10, 000 livebirths. Based on onset and severity of disease, SMA is classified in 4 subtypes, with the infantile SMA type 1, the most common variant, being also the most severe. In particular SMA type 1 babies never achieve the ability to sit independently, and without intervention their life expectancy is less than one year. SMA is caused by mutations in the survival motor neuron 1 ( SMN1 ) gene resulting in insufficient SMN protein levels. SMN2, a nearly identical copy of SMN1, cannot compensate for the loss of SMN1 because of predominant skipping of exon 7 during pre-mRNA splicing. Nusinersen (commercial name SPINRAZA) is a modified antisense oligonucleotide that, administered via consecutive intrathecal injections, modulates the splicing of the SMN2 mRNA transcript to include exon 7, thereby increasing the production of full-length SMN protein. Project: Following the promising results of a large international phase II clinical trial (ENDEAR) where 40% of nusinersen-treated patients reached a motor milestone response versus none on the placebo arm, nusinersen has received FDA and EMA approval and is currently marketed for all types of SMA in US. In several European countries the drug was offered to the trial sites as part of an expanded access program (EAP). GOSH recruited the greatest number of UK trial participants and have the largest UK cohort of patients with SMA type 1. We present the experience and challenges delivering nusinersen under the EAP in a cohort of 20 patients with SMA type 1 treated from March-August 2017. Preliminary data on motor function as systematically assessed using the CHOP-intend scale and the Hammersmith Infant Neurological Examination (HINE scale) will also be presented.